A history of Russia. Part 2 from Peter the Great to Gorbachev - Steinberg, Mark D. 1953-; Teaching Company Limited Partnership (Chantilly, Va. Teaching Co., 2003)
Twelve 30 minute lectures by Mark Steinberg on the history of Russia.
disc 3. lecture 13. Alexander II and the great reforms ; lecture 14. "Nihilists" ; lecture 15. Populists and Marxists ; lecture 16. Paths to revolution - Lenin and Martov ; lecture 17. Lev Tolstoy ; lecture 18. The reign of Alexander III -- disc 4. lecture 19. Nicholas II, the last tsar ; lecture 20. The revolution of 1905 ; lecture 21. Peasant life and culture ; lecture 22. The modern city and its discontents ; lecture 23. Fin-de-siecle culture - Decadence and iconoclasm ; lecture 24. Fin-de-siecle culture - The religious renaissance.
Title from disc label.
Continues disc 1 and disc 2 of part 1
DVD.
Keywords: Russia -- History; Educational films; Filmed lectures; Nonfiction films